Benefits of Employee Performance-Based Training Systems for Companies - Raba, Henricus; Ngamal, Yohanes (Advances In Social Humanities Research, 2024)
The aim of performance-based research is to find out whether training output can improve employee skills such as professionalism, work discipline, productivity, and performance among employees. In carrying out research, use the type of library research, namely research whose object of study uses library data in the form of books as the data source. Performance-based training is suitable for use in complex business environments. Performance-based training has advantages in employee development. Employees are a reliable source of competitive advantage to compete in an ever-changing and competitive business world. Performance-based training is very beneficial for employees and the organization. Performance-based training helps organizations understand the importance of developing employees to be competitive and output-based. Performance-based training will also help companies understand what factors need to be considered when conducting training and how to provide appropriate training to their employees to achieve the output performance of an organization/company so that it continues to improve. Performance-based training as well as output-based training can keep an organization or company surviving and competitive. However, it needs to be understood that successful training must be implemented in parallel with the organization's strategy to achieve the desired training program objectives.